2018
DOI: 10.4067/s0718-50732018000100015
|View full text |Cite
|
Sign up to set email alerts
|

Reacción frente al frío de edificaciones con envolventes vegetales para climas tropicales. Fachadas verdes y cubiertas ajardinadas

Abstract: The main aim of this paper is to demonstrate the benefits that building using natural elements can provide to indoor environments when temperatures are lower. For this purpose, an experimental procedure was used to allow a comparison of the thermal behaviour of four systems: a prototype called Control (no vegetation) and three different combinations of vegetation (roofs and facades) installed in a region of tropical climate. They recorded simultaneously internal surface temperatures, internal air temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results obtained in this study show that the use of green facades in high-Andean buildings has a positive impact on the internal air temperature, reducing the thermal difference by 2,44°C compared to a building without vegetation cover. (10,11) In addition, it has been observed that vegetated roofs are an effective alternative to thermal insulation, as they help retain rainwater and reduce annual runoff volumes in areas where this can be a problem. (12) However, it is important to mention that the maintenance of green facades may be an aspect to consider, as plants require constant watering and care.…”
Section: Figure 2 Thermal Comparison Between Blocks a And Bmentioning
confidence: 99%
“…The results obtained in this study show that the use of green facades in high-Andean buildings has a positive impact on the internal air temperature, reducing the thermal difference by 2,44°C compared to a building without vegetation cover. (10,11) In addition, it has been observed that vegetated roofs are an effective alternative to thermal insulation, as they help retain rainwater and reduce annual runoff volumes in areas where this can be a problem. (12) However, it is important to mention that the maintenance of green facades may be an aspect to consider, as plants require constant watering and care.…”
Section: Figure 2 Thermal Comparison Between Blocks a And Bmentioning
confidence: 99%
“…Construida por el arquitecto François Hennebique para su familia, dispuso todo un plano continuo que cubría la totalidad de la vivienda y que transformó en un jardín con senderos, un huerto e incluso un invernadero para especies exóticas 227 (Figura 2.31). Con el desarrollo de las primeras láminas impermeables (en el periodo de entreguerras, coincidiendo con el Movimiento Moderno y las vanguardias artísticas), estas se colocaron en el nuevo sistema de cubierta plana, sobre los tableros cerámicos, pero se deterioraban con gran rapidez debido a las variaciones de temperatura, a las deformaciones diferenciales y a la incidencia directa de la radiación solar 228 . Aun así, supusieron una revolución en el uso y desarrollo de las cubiertas planas.…”
Section: Historia Y Evolución De La Cubierta Plana Ajardinadaunclassified
“…La llegada del Movimiento Moderno (1925-1965) y el desarrollo de materiales impermeables en Estados Unidos, junto con la arquitectura racional e industrializada de rascacielos y fábricas, supuso un verdadero auge de las cubiertas planas transitables 230 , ahora con poco peso y con materiales impermeables, aunque con el paso del tiempo, como ya se ha comentado, se deterioraran con rapidez. Esta revolución constructiva llega a las cubiertas ajardinadas de la mano de los cinco puntos de la nueva arquitectura de Le Corbusier (1926).…”
Section: Historia Y Evolución De La Cubierta Plana Ajardinadaunclassified
See 2 more Smart Citations